La contribution des gouvernements provinciaux et territoriaux à l’épanouissement des communautés francophones en milieu minoritaire Un premier bilan et quelques prospectives - Bourgeois, Daniel; Denis, Wilfrid; Dennie, Donald; Johnson, Marc L. (Institut canadien de recherche sur les minorités liguistiques, 2006)
Depuis près de quarante ans, les gouvernements des neuf provinces et des trois territoires à majorité anglophone œuvrent à promouvoir la langue et la culture françaises en milieu minoritaire, contribuant ainsi à l’épanouissement des communautés francophones. En effet, malgré l’importance de la contribution fédérale, plusieurs secteurs qui relèvent de la compétence exclusive des provinces et des territoires – l’éducation, la santé et les services sociaux et municipaux – contribuent à la vitalité des communautés francophones. L’absence de littérature sur les interventions des provinces et des territoires en matière de langues officielles porterait à croire qu’elles sont rares, voire inexistantes, ou qu’elles visent plutôt à entraver l’épanouissement des communautés francophones. Il n’en est rien. Une compilation et une analyse des interventions provinciales et territoriales dans le domaine des langues officielles étaient donc de mise. Dans un premier temps, il fallait préciser la nature de ces interventions et en produire une compilation systématique. Dans un deuxième temps, il importait d’en dresser un bilan critique. Nous avons par la suite proposé quelques prospectives immédiates et à long terme. Notre recherche porte sur neuf secteurs d’activité : (1) les communications et les services au public en français, (2) la petite enfance, (3) la santé et le bien-être, (4) la justice, (5) les arts et la culture, (6) le développement économique, (7) les groupes cibles (les jeunes, les aînés, les femmes) (8) l’immigration et (9) les municipalités. À la section sur la santé et le bien-être, les thèmes suivants sont abordés: a) Législation et jurisprudence; b) Politique; c) Programmes et services; d) Publications et documentation; e) Appui financier et institutionnalisation; f) Formation professionnelle.
Rapport préparé pour la Conférence ministérielle sur la francophonie

Évaluation de l’offre active des services de santé de première ligne - Comité santé en français de Fredericton (Groupe Progecom communication et stratégies d’entreprise, 2006)

Communicative sensitivity in the bilingual healthcare setting: A qualitative study of language awareness - Irvine, Fiona. E.; Roberts, Gwerfyl. W.; Jones, Peter; Spencer, Llinos. H.; Baker, Colin. R.; Williams, Cen (Journal of Advanced Nursing, 2006)
Aim. This paper reports on the second phase of a national study in Wales. The research aimed to assess the level of Welsh language awareness amongst healthcare professionals across Wales, and to identify the factors that enhance language choice within service delivery. Background. The literature suggests that language sensitive healthcare practice is central to ensuring high quality care. However, it is evident that language barriers continue to compromise the quality of care within nursing and other health services. One issue that has received little attention is the level of language awareness that healthcare professionals currently demonstrate. Furthermore the factors that influence language choice for bilingual/multilingual speakers are not well explored in the literature. Methods. The study involved semi-structured interviews with a range of healthcare professionals in acute and community settings across Wales. Using a systematic sampling matrix, a purposeful sample of 83 professionals was selected to participate. Twenty-seven of the respondents were nurses, health visitors and midwives. The interviews focussed on the factors that facilitate or impede language sensitive healthcare practice. All interviews were audiotaped and, using a framework analysis approach, conceptual codes were developed and defined and categories and sub-categories were constructed to create thematic charts. Findings. Three main themes were identified: care enhancement, which focussed on the process and outcome of offering language choice to bilingual patients; organizational issues, which reflected issues relating to the infrastructure of service provision; and training implications, which focused on Welsh language learning in health care. Conclusions. Complex dynamics of language use are in operation within bilingual healthcare settings and organizational as well as individual factors are important in facilitating appropriate language use. Many of the issues highlighted are not peculiar to the Welsh context, but apply to healthcare settings across the world, where other minority languages are in use.

Les services de santé au Canada : une perspective linguistique - Lacroix, Frédéric (L'Action nationale, 2006)

Accès aux services de santé et aux services sociaux en anglais au Québec. Rapport de données de base 2005-2006 - Pocock, Joanne (Réseau communautaire de santé et de services sociaux, 2006)

Préparer le terrain. Soins de santé primaires en français dans le Sud de l'Ontario. Rapport régional - Réseau franco-santé du Sud de l'Ontario (2006)

Préparer le terrain : soins de santé primaires en français en Ontario. Rapport provincial - Réseau francophone de santé du Nord de l’Ontario; Réseau de santé en français du Moyen-Nord de l’Ontario; Réseau franco-santé du Sud de l’Ontario; Réseau des services de santé en français de l’Est de l’Ontario (2006)

Des services de santé en français dans un Nord en mutation. Un défi intercommunautaire - Réseau Santé en français au Nunavut (Association des Francophones du Nunavut, Santé en français au Nunavut, 2006)

The effects of a language barrier in a South African district hospital - Schlemmer, A.; Mash, B. (South African Medical Journal = Suid-Afrikaanse Tydskrif Vir Geneeskunde, 2006)
BACKGROUND: Communication between health workers and patients at Hottentots Holland Hospital (HHH) is hindered by staff and patients not speaking the same language. HHH is a district hospital in the Cape Town Metropolitan District of the Western Cape where staff mainly speak Afrikaans or English and a large number of patients mainly Xhosa. OBJECTIVES: The study aimed to explore the effects of this language barrier on health workers and patients at HHH. DESIGN: Three focus group interviews were held with 21 members of staff and 5 in-depth patient interviews were conducted. RESULTS: The language barrier was found to interfere with working efficiently, create uncertainty about the accuracy of interpretation, be enhanced by a lack of education or training, cause significant ethical dilemmas, negatively influence the attitudes of patients and staff towards each other, decrease the quality of and satisfaction with care, and cause cross-cultural misunderstandings. CONCLUSION: The effects of the language barrier were considerable and persistent despite an official language policy in the province. The training and employment of professional interpreters as well as teaching of basic Xhosa to staff are recommended.
Keywords: Communication Barriers; Health Services Accessibility; Hospitals; District; Humans; Language; Multilingualism; Outcome Assessment; Health Care; Professional-Patient Relations; South Africa; Surveys and Questionnaires